2018
DOI: 10.1177/0042098018757873
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the barriers: How urban housing ownership has changed migrants’ settlement intentions in China

Abstract: Since the abolition in China of unequal regulations and controls related to the urban labour market and rural–urban migration in recent years, attention has been paid to migrants’ settlement intentions and their integration into host cities. Settlement channels have become more diverse and more accessible to migrants, because of relaxed institutional constraints and the advanced market mechanism, which are essential to the pace and process of urbanisation, and welfare and service provisions in host cities. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 28 publications
4
56
0
Order By: Relevance
“…This is especially true in smaller cities where hukou status does not make as much of a difference [30]. In these locales with fewer institutional hurdles, migrants have adapted and found other ways to settle down [31,32]. Others maintain that institutional barriers are the main reason for migrants' low homeownership rate.…”
Section: Migrant Homeownership and Social Security Participation In Cmentioning
confidence: 99%
“…This is especially true in smaller cities where hukou status does not make as much of a difference [30]. In these locales with fewer institutional hurdles, migrants have adapted and found other ways to settle down [31,32]. Others maintain that institutional barriers are the main reason for migrants' low homeownership rate.…”
Section: Migrant Homeownership and Social Security Participation In Cmentioning
confidence: 99%
“…Previous studies focused on the household registration system (hukou), which was established in the 1950s, as a key constraint of migrants' settlement because the hukou system prevents migrants from obtaining equal rights, such as employment, health care, and education, to those of local hukou holders in the host city (Li & Duda, 2010;Logan, Fang, & Zhang, 2009). However, many scholars have proved that the effect of the hukou system is weakening along with its ongoing reform (Tao, Hui, Wong, & Chen, 2015;Yang & Guo, 2018). Instead, owning a house is regarded as a vitally important indicator for migrants' permanent settlement and sense of belonging in the host city (Xie & Chen, 2018); homeownership is also a more flexible way to avoid the restrictions of the hukou system, and to access the city's welfare system (Yang & Guo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, many scholars have proved that the effect of the hukou system is weakening along with its ongoing reform (Tao, Hui, Wong, & Chen, 2015;Yang & Guo, 2018). Instead, owning a house is regarded as a vitally important indicator for migrants' permanent settlement and sense of belonging in the host city (Xie & Chen, 2018); homeownership is also a more flexible way to avoid the restrictions of the hukou system, and to access the city's welfare system (Yang & Guo, 2018). However, the homeownership rate of migrants is rather low; renting or living in poor urban villages are still the main housing choices of migrants (Tao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite strict population control through the hukou system, for example, rural migrants are more likely to concentrate in larger cities, especially the first-tier cities (Zhu, Xiao, & Lin, 2015). Many rural migrants avoid the institutional hurdle of obtaining a local urban hukou and become de facto permanent residents through purchasing urban housing in their host cities (Yang & Guo, 2018). While hukou reforms have increased opportunities to obtain urban hukou in small and medium-sized cities, they have not resulted in a significant surge in the number of rural residents moving to settle in cities by giving up their rural hukou.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Liu, Wang, and Chen (2017), for instance, demonstrated the existence of a sorting process in which the rural migrants who were more inclined to permanently stay in cities would strive to seek formal urban housing. Indeed, for many rural migrants in China, purchasing urban housing has become an easier and more flexible way of achieving de facto permanent settlement in the city (Yang & Guo, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%